Multi-functional approach in forest landscape management planning: an application in Southern Italy - Paletto, A.; Ferretti, F.; Cantiani, P.; De Meo, I. (Forest Systems, 2012)
Forest Landscape Management Plan (FLMP) is intended to have an intermediate role between forest management plans on a regional level and forest management on a unit level. FLMP addresses long-term management issues, with special attention to social and environmental functions, normally not meticulously considered when working on a single forest property level. This paper presents a method to evaluate forest multifunctionality, in order to define management guidelines and support forest planning. A FLMP was conducted in a district of the Basilicata region (Italy). A total of 92 inventory plots comprising the main forest types: i) turkey oak, Hungarian oak, and sessile oak forests (Quercus cerris L. dominant), ii) downy oak forests (Quercus pubescens Willd. dominant), iii) Mediterranean evergreen oak forests (Quercus ilex L. dominant), were considered. Technicians evaluated the multifunctionality of each area by estimating — in the context of an Index of Importance of Function (I) — the capacity of each forest to fulfil different functions. The index was successively aggregated according to forest type and forest system (high forest and coppice). The results showed that the higher level of multifunctionality was found in the high forests. According to the synthetic indicators of multifunctionality, the turkey oak forests obtained the highest values among all forest types. The last part of the paper illustrates an approach to multi-functional forest management, analysing how different silvicultural systems are able to fulfil the main forest functions. This method, as shown in the results, seems to provide a useful support for technicians to evaluate multifunctionality related to forest types and different silvicultural treatments.